Резьба по дереву: издания для досуга / А.Н.Виноградов - Виноградов А. Н. (Хэлтон, 2005)
Экземпляры: ф.5 (2005) / Инвентарный номер: 49296 / Цена: 32.34 / Сис.шифр: 85.12 / Авт.знак: В 49 / ГРНТИ: 18.31.51 / ББК: 85.125